2008
DOI: 10.1128/jb.01670-07
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Swarming Motility andflhDCSmExpression by RssAB Signaling inSerratia marcescens

Abstract: Serratia marcescens cells swarm at 30°C but not at 37°C, and the underlying mechanism is not characterized. Our previous studies had shown that a temperature upshift from 30 to 37°C reduced the expression levels of flhDC Sm and hag Sm in S. marcescens CH-1. Mutation in rssA or rssB, cognate genes that comprise a twocomponent system, also resulted in precocious swarming phenotypes at 37°C. To further characterize the underlying mechanism, in the present study, we report that expression of flhDC Sm and synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…5C) strongly suggest that FliA is able to activate ShlA expression by direct induction of shlBA transcription. FliA-mediated regulation of ShlA expression also helps to explain the results obtained by Soo et al in an S. marcescens CH-1 pigmented strain (43) showing that the RssAB system could partially repress shlBA in an FlhDC-dependent manner. …”
Section: Discussionsupporting
confidence: 55%
“…5C) strongly suggest that FliA is able to activate ShlA expression by direct induction of shlBA transcription. FliA-mediated regulation of ShlA expression also helps to explain the results obtained by Soo et al in an S. marcescens CH-1 pigmented strain (43) showing that the RssAB system could partially repress shlBA in an FlhDC-dependent manner. …”
Section: Discussionsupporting
confidence: 55%
“…The class I master operon, flhDC, encodes the FlhD 2 C 2 complex which is an activator of s 70 -dependent transcription from class II promoters (Chilcott and Hughes, 2000). We have previously shown that synthesis of flagella and flhDC expression were significantly increased in the rssA mutant (S. marcescens CH-1 DrssA) (Soo et al, 2008). The RssA sensor kinase phosphorylates the RssB response regulator (Wei et al, 2005a).…”
Section: Introductionmentioning
confidence: 98%
“…The RssA sensor kinase phosphorylates the RssB response regulator (Wei et al, 2005a). Phosphorylated RssB (RssB-P) binds to the flhDC promoter (Soo et al, 2008). Missense mutation on histidine 248 of RssA and aspartate 51 of RssB led to abnormal swarming phenotype, unphosphotransfer from RssA to RssB, and unbinding to the flhDC and rssB promoters by RssB (Wei et al, 2005a;Soo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…S. marcescens swarms on Luria-Bertani (LB) agar surfaces at 30°C, but not at 37°C (36). Our previous studies showed that activation of a bacterial two-component system, RssAB, comprising a sensor kinase, RssA, and a response regulator, RssB, inhibited swarming and reduced hemolysin production in S. marcescens CH-1 at 37°C (36,57,63). In contrast, loss of rssBA resulted in a precocious swarming phenotype and a significant increase in hemolytic activity (36).…”
mentioning
confidence: 99%
“…Recently, we showed that activated RssAB signaling directly represses expression of flhDC and swarming in S. marcescens CH-1 at 37°C (57). FlhDC is known to be a major checkpoint of swarmer cell differentiation in S. marcescens MG1 (formerly Serratia liquefaciens MG1) (13) and is also involved in early stages of biofilm formation in Escherichia coli (48).…”
mentioning
confidence: 99%